Vertical distribution of mesozooplankton biomass in relation to oxygen minimum layer in the Andaman Sea - Madhu, N V; Jyothibabu, R; Ramu, K; Sunil, V; Gopalakrishnan, T C; Nair, K K C (Indian Journal of Fisheries, 2011)
Mesozooplankton biomass in the upper 1000m of the Andaman Sea was studiedduring February 1999 providing baseline information on stratification ofmesozooplankton of the area. The distribution of mesozooplankton biomass isrelated to the oxygen minimum layer (